Integrated management systems for the construction industry in Singapore - Goh, Thiam Lai. (2008)
This dissertation examines similarities between the ISO 9001 quality management system, ISO 14001 environment management system and OHSAS 18001 occupational health and safety management system, shares approaches used by two construction companies in their successful implementation of an integrated management system and provides examples of documentation that have withstood the scrutiny of certification bodies.